Anatomy of murder - Robertson, Imogen, 1973- (Pamela Dorman Books, 2012)
Amateur detectives in Georgian England, Harriet Westerman and Gabriel Crowther investigate the drowning of a man in the Thames and discover that he may have been part of a plot to betray England's secrets to France.